The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1161/01.hyp.0000027134.14160.1d
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain-Binding Protein(s) From Human Plasma

Abstract: Abstract-Conservation of the binding site on mammalian Na ϩ ,K ϩ -ATPase for cardiac glycosides and the importance of the Na ϩ pump in mammalian cellular physiology has stimulated the search for a mammalian analog of these plant compounds. One candidate, isolated from brain and blood, appears to be ouabain itself or a closely related isomer, the ouabain-like compound. Little is known about the circulating form. Because human steroid hormones circulate with carrier proteins, we produced a ouabain-specific monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…No apparent toxicity was observed, however, in the present study. Hence, either the actual free OLC concentration in plasma is lower than that one determined after extraction (eventually caused by its binding to cardiac glycoside binding proteins in blood 20,21 ) or the sodium pump is not yet inhibited within the time interval studied because of the slow on-rate in forming the inhibitory and almost irreversible ouabain-Na ϩ /K ϩ -ATPase complex. 22 A transient increase of endogenous ouabain may not lead to inhibition of the pump, although a rapidly dissociable ouabain-Na ϩ /K ϩ -ATPase complex might be formed.…”
Section: Discussionmentioning
confidence: 91%
“…No apparent toxicity was observed, however, in the present study. Hence, either the actual free OLC concentration in plasma is lower than that one determined after extraction (eventually caused by its binding to cardiac glycoside binding proteins in blood 20,21 ) or the sodium pump is not yet inhibited within the time interval studied because of the slow on-rate in forming the inhibitory and almost irreversible ouabain-Na ϩ /K ϩ -ATPase complex. 22 A transient increase of endogenous ouabain may not lead to inhibition of the pump, although a rapidly dissociable ouabain-Na ϩ /K ϩ -ATPase complex might be formed.…”
Section: Discussionmentioning
confidence: 91%
“…Serum albumin is considered so far to fulfill the transport function for cardiotonic steroids in blood,18 but the dissociation constants of the cardiac glycoside albumin complexes are well above therapeutic digoxin concentrations. Recent search for a specific cardiac glycoside binding protein in serum resulted in the isolation of several proteins with high affinity for ouabain, that is, a protein of 50 kDa with unknown amino acid sequence and function;17 a 14.4‐kDa protein representing the plasmin‐cleaved carboxy‐terminal end of the heavy chain of IgG2 and IgG1;19 and an immunoglobulin‐like protein with bands of 80, 50, and 25 kDa in SDS‐PAGE representing ≤ 0.5% of the IgG fraction 20. In our trials to characterize the previously described cardiac glycoside binding protein from bovine serum17 any further, we were confronted with the observation that, in addition to the formerly described 50‐kDa band, a 90‐kDa protein also became visible in affinity labeling with HDMA.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, Antolovic et al (1998) isolated from mammalian plasma and kidneys a specific cardiac glycoside-binding globulin with higher- and lower-affinity binding sites for ouabain and possibly for endogenous CTS. Later, CTS-binding protein was identified as a fragment of IgG (Komiyama et al, 1998; Parhami-Seren et al, 2002). The importance of CTS-binding protein(s) on the function of CTS has not been studied consistently yet; however, Antolovic et al (2000) suggested that binding of CTS to and unbinding of CTS from this transport protein may be involved in a rapid and transient 36-fold rise of EO in response to exercise.…”
Section: Salt-sensitive Hypertension Concept Of Natriuretic Hormmentioning
confidence: 99%